The Use of Kamishibai as a Visual Media in Tadoku Courses to Improve Japanese Speaking Skills for Japanese Language Students at the Faculty of Teacher Training and Education, Universitas Riau - Bestari, Intan; Merri Silvia Basri; Yenny Aristia Nasution (The Future of Education Journal, 2025)
This study aims to determine the effectiveness of using kamishibai as a visual medium in the tadoku course to improve Japanese speaking skills among students of the Japanese Language Education Program at the Faculty of Teacher Training and Education, Universitas Riau. Kamishibai is a traditional Japanese storytelling medium that combines narrative with illustrations, while tadoku refers to extensive reading using simple and enjoyable texts. The research employed an experimental method with a one-group pre-test and post-test design involving 20 first-year students from class A, academic year 2024. Data were collected through oral tests focusing on five aspects: pronunciation, grammar, vocabulary, fluency, and content. The pre-test results showed an average score of 56.4, categorized as “poor,” while the post-test average increased to 70.2, categorized as “good.” A normality test confirmed that the data were normally distributed, and a paired sample test revealed a significance value of < 0.05, indicating a statistically significant improvement. These results demonstrate that the use of kamishibai as a visual aid is effective in enhancing students’ Japanese speaking abilities in the tadoku course.